El Diseño Curricular por Competencias Laborales en la Carrera de Ingeniero Agrónomo de la Universidad de Guanajuato - Córdova Duarte, Gabriel; Ruiz Rueda, Héctor; Montesinos Silva, Genaro; Barbosa Jaramillo, Elva Rosa; Mendoza Celedon, Briseida (Acta Universitaria, 2000)
This work was done to meet the demand for modernizing the curriculum in agronomy. It is based on a documental review following the methodology of Hanel [et al.], in 1997. The results were: identification of the main problems in agriculture, agronomy, and the career of agronomist, and in educational policies and university philosophy; determination of the four careers in agronomy; definition of the graduate profile in terms of knowledge, ability, attitudes, and values; requirement of professors with postgraduate studies and pedagogical and axiological updating; a flexible curricular structure tied to the logic of the discipline; an integral evaluation from curriculum to administration; identification of complementary activities that contribute to the formation of the student; the socializing of the curriculum with participation of academics and their introduction in distinct forums. Thus the institutional demand was met in a search for excellence in student preparation, quality in the educational process, and encouragement of evaluation practices.